Charging scheduling strategy for different electric vehicles with optimization for convenience of drivers, performance of transport system and distribution network. (1st March 2020) - Luo, Yugong; Feng, Guixuan; Wan, Shuang; Zhang, Shuwei; Li, Victor; Kong, Weiwei
Abstract: With the popularization of electric vehicles, large-scale electric vehicle charging may negatively impact drivers, the power grid, and traffic conditions. Currently, research conducted on the charging and battery swap of electric vehicles is insufficient. The objective for optimization and the type of electric vehicle proposed by other papers are limited in scope. In order to achieve an overall optimization of the whole system, the driver demands, the road traffic speed, the number of vehicles in the charging station and the charging network load are considered in the development of the charging scheduling strategy for electric vehicles. Such a strategy can further enhance driver convenience in terms of making decisions for charging and battery swap of electric vehicles. Moreover, different types of electric vehicles are taken into account for a more practical proposed scheduling strategy. Utilizing MATLAB and MATPOWER, a simulation platform is established to validate the strategy. Simulation results demonstrate that the proposed scheduling strategy can relieve local traffic jams, smooth network load curve, increase safety and economy of the power network, and decrease the number of charging electric vehicles in station. Ultimately, this plan can simultaneously reduce waiting time of charging and increase the operational efficiency of charging stations.